Monitoring of thermal fields on surface of alkali halide single crystals grown from the melt - Sidletskiy, O.Ts.; Goriletsky, V.I.; Grinyov, B.V.; Sumin, V.I.; Sizov, O.V.; Tymoshenko, М.N. (Functional Materials, 2005)
Experimental data on brightness temperature distribution on the upper butt surface of large alkali-halide single crystals grown from the melt using automated semi-continuous method were obtained for the first time using radiation thermometry. It has been shown that different thickness of condensate deposited on the crystal surface from the vapor phase of the melt becomes a cause of significant mistakes at non-contact measurements. Crystal surface emissivity value and minimal thickness of the condensate has been determined experimentally allowing one to obtain correct temperature values when monitoring the ingot surface using infrared thermometer.